Pengaruh Model Pembelajaran Tipe Kooperatif Tipe Jigsaw Terhadap Pemahaman Konsep dan Keterampilan Berpikir Kritis Siswa kelas V SD Negeri 101090 Gunung Tua Pada Mata Pelajaran Bahasa Indonesia Tahun Ajaran 2022/2023 - Siregar, Ummi Aisyah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Students' critical thinking skills can be influenced by the selection of learning models. This study aims to: (1) determine the level of students' understanding of the concept after the jigsaw type cooperative learning. (2) knowing the level of students' thinking ability after doing jigsaw cooperative learning. (3) knowing the effect of jigsaw type learning method on conceptual understanding ability. (4) knowing the effect of jigsaw type learning method on critical thinking skills. The type of experimental research used was Quasi-Experimental. The research subjects consisted of 65 students. Samples were taken from the subject population consisting of 33 students in class Va (control group) and 32 students in class Vb (experimental group). The dependent variable consisted of conceptual understanding and thinking skills from student learning outcomes. The independent variables are the jigsaw method and the lecture method. The technique of collecting data on learning outcomes uses multiple choice tests and for students' understanding of concepts and thinking skills activities using a questionnaire of student activity observation sheets. Learning outcomes are compared based on criteria and learning outcomes data are analyzed by gain test and t test. The results showed that the jigsaw method had a significant effect on conceptual understanding and thinking skills of fifth grade students at SDN 101090 Gunung Tua in Indonesian. The activity of understanding concepts and thinking skills of students in the experimental class achieved very high criteria, while those in the control class only reached the sufficient criteria. The average posttest value of the experimental group is better than the control group. The mean posttest of the experimental group was 72.15 and the mean posttest of the control group was 64.21. This shows that the g gain index for the experimental group is 74.25 (high) while the g control group is 64.72 (moderate). The results of the t test show that the value of tcount (2.474) ttable (1.992) means that the Jigsaw method has an effect on learning outcomes in Indonesian and Sig. (2-tailed) 0.05 which is 0.028. These results conclude that there is a significant difference between the learning outcomes of the experimental class and the control class. Keywords: Jigsaw Method, Understanding of concepts, critical thinking skills, Indonesian